ЗАСТОСУВАННЯ АКТИВНИХ ФІЛЬТРІВ ДЛЯ ЗМЕНШЕННЯ ВТРАТ ЕНЕРГІЇ ТРИФАЗНИХ СИСТЕМ ЕЛЕКТРОПОСТАЧАННЯ - Артеменко, М.Ю.; Каплун, В.В.; Бобровник, В.М.; Поліщук, С.Й. (Інститут електродинаміки НАН України, Київ, 2022)
A new analytical condition of expedient application of shunt active filters (SAF) and formula for estimating the energy saving effect from their installation in three-phase power supply systems under stationary load have been obtained. It is proposed to evaluate the energy-saving effect from the use of SAF under periodically varying load by the energy losses gain coefficient, for which the method of determination is given. The application of the method is illustrated by the calculation of the energy-saving effect by the results of weekly monitoring the electricity consumption in the KNUTD hostel number 7. References 9, table 1, figures 2.